Qiro'ah Fi Kitab Al-Lisaniyyat Fi Ats-Tsaqofah Al-'Arabiyyah Al-Mu'ashiroh (Dirosah Tahliliyyah Naqdiyyah Fi Qodoya At-Talaqqi wa Isykalatih) ‘Ardan Wa Naqdan - Sholah Abdussalam Qosim Al-Haigami (Indonesian Journal of Arabic Studies, 2019)
This study aims to review the book by Dr. Hafez Ismaili Alawi entitled ‘Al-Lisaniyyat Fi Ats-Tsaqofah Al-'Arabiyyah Al-Mu'ashiroh (Dirosah Tahliliyyah Naqdiyyah Fi Qodoya At-Talaqqi wa Isykalatih 'published by Dar al-Kitab Al-Jadid Al-Muttahida Beirut city. The study was conducted using a critical review of the contents of the book in addition to describing the main ideas of the authors related to linguistic science in modern Arabic culture